1995
DOI: 10.1002/art.1790080110
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy, pain, and physical activity among fibromyalgia subjects

Abstract: Purpose. The purpose of this study was to examine the effects of self‐efficacy on self‐report pain and physical activities among subjects with fibromyalgia (FM). In addition, descriptive statistics of the Arthritis Impact Measurement Scale (AIMS), a measure developed for use with arthritis patients, were reported. Methods. Seventy‐nine subjects with FM, as classified by the American College of Rheumatology (ACR) criteria, completed the Visual Analogue Scale for Pain, the AIMS, and the Arthritis Self‐Efficacy S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 14 publications
8
77
0
4
Order By: Relevance
“…Thus, the use of these resources would reduce functional limitation. In this regard, previous studies have demonstrated the influence of these variables on physical functioning in FM (Buckelew et al 1995;Culos-Reed & Brawley, 2003;Fontaine et al, 2010), and various treatment programs have mentioned that self-efficacy is fundamental to predict physical functioning (Buckelew et al, 1995;Oliver & Cronan, 2002;Rivera et al 2004;Schachter et al, 2003). The presence of positive emotions and cognitive resources reflect better physical functioning and reduced clinical symptoms in fibromyalgia (Arnold et al, 2006;Hassett et al, 2000;Porter-Moffitt et al 2006;Suhr, 2003).…”
Section: An Integral Explanatory Model For Fibromyalgiamentioning
confidence: 97%
See 4 more Smart Citations
“…Thus, the use of these resources would reduce functional limitation. In this regard, previous studies have demonstrated the influence of these variables on physical functioning in FM (Buckelew et al 1995;Culos-Reed & Brawley, 2003;Fontaine et al, 2010), and various treatment programs have mentioned that self-efficacy is fundamental to predict physical functioning (Buckelew et al, 1995;Oliver & Cronan, 2002;Rivera et al 2004;Schachter et al, 2003). The presence of positive emotions and cognitive resources reflect better physical functioning and reduced clinical symptoms in fibromyalgia (Arnold et al, 2006;Hassett et al, 2000;Porter-Moffitt et al 2006;Suhr, 2003).…”
Section: An Integral Explanatory Model For Fibromyalgiamentioning
confidence: 97%
“…In this sense, lower selfefficacy regarding symptoms lead to greater negative affect which in turn affect functional limitation. Previous studies have established a relationship between self-efficacy for pain and functional limitation (Buckelew et al 1995;Jegede, 2006;Martin-Aragon et al, 2001M Mueller et al 2003Oliver & Cronan, 2002;Theadom et al, 2007;Velasco et al, 2008), although they did not include affect as a mediating variable. Functional capacity is a major source of concern in patients with FM as they face limitations in carrying out different activities, especially in activities of daily life which they regard as fundamental.…”
Section: Affect As a Mediator Between Perception Of Control And Functmentioning
confidence: 98%
See 3 more Smart Citations